Potential Antimicrobial Activity of Galloyl-Flavonoid Glycosides From Woodfordia uniflora Against Methicillin-Resistant Staphylococcus aureus - Yu, Jae Sik; Kim, Ji-Hoon; Rashan, Luay; Kim, Inseo; Lee, Wonsik; Kim, Ki Hyun (Frontiers in Microbiology, 2021)
Antibiotic-resistant infections are a growing problem; to combat multi-drug resistant bacterial infections, antibiotics with novel mechanisms of action are needed. Identification of potent bioactive natural products is an attractive avenue for developing novel therapeutic strategies against bacterial infections. As part of our ongoing research to explore bioactive natural products from diverse resources, we investigated the antimicrobial compounds from Woodfordia uniflora, a flowering shrub unique to the Dhofar region of Oman. The plant has been used as a remedy for skin infections in Oman. However, to date, no study has examined the antimicrobial compounds in W. uniflora. Phytochemical analysis of the methanolic extract of W. uniflora leaves in combination with LC/MS-based analysis allowed us to isolate and identify four flavonoid-type analogs (1 - 4), procyanidin B3-3-O-gallate (1), rhamnetin 3-O-(6′′-galloyl)-β-D-glucopyranoside (2), rhamnetin 3-O-α-L-rhamnopyranoside (3), and quercetin 3-O-(6′′-galloyl)-β-D-glucopyranoside (4). The isolates have a novel mechanism of action; the compounds inhibit biofilm formation in methicillin-resistant Staphylococcus aureus (MRSA) and synergize with methicillin. Our metabolite analysis revealed that this synergizing activity by compounds was achieved by remodeling metabolism including central carbon metabolism and glutamine biosynthesis that resulted in abnormal cell formation and reduction in biofilm formation of MRSA. Taken together, these findings provide experimental evidence that rhamnetin 3-O-(6′′-galloyl)-β-D-glucopyranoside (2) and quercetin 3-O-(6′′-galloyl)-β-D-glucopyranoside (4) can be considered as potential therapeutic agents for the treatment of methicillin-resistant S. aureus-associated diseases.